2009
DOI: 10.1143/apex.2.121002
|View full text |Cite
|
Sign up to set email alerts
|

Light Emission from InGaN Quantum Wells Grown on the Facets of Closely Spaced GaN Nano-Pyramids Formed by Nano-Imprinting

Abstract: In x Ga 1Àx N/GaN quantum wells have been grown on the f10 11g facets of dense arrays of self-assembled GaN nano-pyramids formed by selective area growth and characterised by high spatial resolution cathodoluminescence. The pyramids are shown to have significantly reduced defect (green-yellow) band emission and the quantum well luminescence is correspondingly intense. The peak energy of this luminescence is shown to blue-shift as the sampled region is moved up the pyramid facets, revealing that InN incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…Next, hexagonal GaN pyramids were grown with MOVPE, using a condition at a low temperature (1150 °C) and a low V/III ratio 4, 5: the partial pressures of TMG and NH 3 were 0.093 and 74.0 mbar, respectively. We stopped the growth of GaN pyramids in the middle so that we can observe both semi‐polar {11–22} planes and polar (0001) planes.…”
Section: Methodssupporting
confidence: 47%
“…Next, hexagonal GaN pyramids were grown with MOVPE, using a condition at a low temperature (1150 °C) and a low V/III ratio 4, 5: the partial pressures of TMG and NH 3 were 0.093 and 74.0 mbar, respectively. We stopped the growth of GaN pyramids in the middle so that we can observe both semi‐polar {11–22} planes and polar (0001) planes.…”
Section: Methodssupporting
confidence: 47%
“…An increasing indium flow leads to a higher strain and the aforementioned redistribution of the indium, resulting in the expected formation of local composition fluctuations 30. Recent measurements by another group 31 showed that a redistribution of Indium can be also observed for smaller pyramids, in this case, however, the indium incorporates preferably at the base of the pyramid, leading in a redshift toward the pyramid base.…”
Section: Resultsmentioning
confidence: 92%
“…1(b)] after the short GaN facet recovery growth. With sufficient growth time, the NR tips would form into a self-limiting pyramid shape, [27][28][29] with the slower growing and more stable semipolar f1-101g facets causing extinction of the faster growing planes 30 at convex surfaces. Similarly, extinction of the faster growing a-planes will occur on the vertical sidewalls of the NRs, leaving structures of hexagonal cross-section, terminated by m-planes.…”
Section: Characterization Of Indium Gallium Nitride Layersmentioning
confidence: 99%